Cómo mirar una parte del mundo: el vocabulario del cuerpo en una lengua amerindia - Bernárdez, Enrique (Caplletra. Revista Internacional de Filologia, 2006)
This paper analyses the vocabulary of body parts in Cha’palaachi, an Amerindian language of the Republic of Ecuador. A number of basic roots refers to (a) forms or (b)parts of the body, although in some cases reference is made to general areas more than to specific parts. These areas, as well as the general vocabulary of forms, points to the importance of spatial elements in Cha’palaachi, which is also identifiable in other parts of the vocabulary and grammar. A significant point is that the body-part terms are organised on the basis of the reference to form, in such a way that the body-part element itself is only of secondary importance. Metaphorical and metonymic extensionis more frequently applied to these form-terms than to the body-part terms proper.